2022
DOI: 10.1021/acs.jafc.2c01034
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization and Potential Mechanism of the Anti-Asthmatic Activity of a Subfraction from Schisandra chinensis Fruit Extract

Abstract: Schisandra chinensis fruit is a widely edible and medicinal resource, whose extract had a good inhibitory effect on airway inflammation in asthmatic mice. However, the main active components remain unknown. In this work, we found that PET2, a subfraction of its ethanolic extract petroleum ether, displayed significant anti-inflammatory effects in interleukin (IL)-4/tumor necrosis factor (TNF)-α-stimulated BEAS-2B cells. Meanwhile, in the ovalbumin (OVA)-induced allergic asthma mice model, PET2 (200 and 400 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 47 publications
4
3
0
Order By: Relevance
“…the higher the administered dose, the stronger the e cacy in TNF-α, IL-6, and IL-10. These results suggested that Schisandrin, Schisandrol B, Schisandrin A, Schisandrin B, and Gomisin D caused an antiin ammatory effect, combined with previous reports that RSC can treat asthma by anti-in ammatory [21], implying the improvement of the e cacy of WSC was related to the 5 Q-markers.…”
Section: E Cacy Comparison Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…the higher the administered dose, the stronger the e cacy in TNF-α, IL-6, and IL-10. These results suggested that Schisandrin, Schisandrol B, Schisandrin A, Schisandrin B, and Gomisin D caused an antiin ammatory effect, combined with previous reports that RSC can treat asthma by anti-in ammatory [21], implying the improvement of the e cacy of WSC was related to the 5 Q-markers.…”
Section: E Cacy Comparison Resultssupporting
confidence: 75%
“…In addition, all 5 components exerted the anti-in ammatory effects in a dose-dependent manner, combined with previous reports that RSC and WSC can treat asthma by anti-in ammatory(Fig. 10B) [21], implying that Schisandrol A, Schisandrol B, Schisandrin A, Schisandrin B, and Gomisin D was Q-markers re ecting the e cacy of the decoction pieces.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The mice were given intragastric administration every other day from the 27th day onward, 30 min before the OVA challenge. The dose of administration groups was determined based on our previous research on the anti-asthmatic activity of a subfraction from Schisandra chinensis fruit extract, literature reference, and pre-experiment ( Li et al, 2022 ). At last, the mice were killed on day 49 after overnight fasting, mouse lung tissues were collected for histological examination, and blood samples were collected for Elisa examination.…”
Section: Methodsmentioning
confidence: 99%
“…The clinical efficacy of a decoction results from the main components of the decoction. Many scholars have conducted systematic analyses of the chemical components in the ethanol extract of RSC [ 16 , 17 ]. However, it is still unclear which components can be extracted from the decoction and which components can be absorbed by blood during treatment, making it difficult to establish a specific quality evaluation standard for decoction pieces.…”
Section: Introductionmentioning
confidence: 99%